Czech and Slovak railways : three decades of change, 1990 2020s - Fender, Keith (World railways series, 2021)
"The Czech Republic and Slovakia emerged as independent countries in 1993, as joint successors of the former Czechoslovakia. Having once been a single country, with a single national railway operator, the change was significant, although both countries, and their railways, still have a lot in common. Loco types have changed through modernisation and rebuilding, and both countries have retained very different narrow-gauge systems. Both countries have invested in modern fleets, and rail freight has boomed thanks to globalisation and EU membership. Spanning three decades, this book explores the history and railways of both countries and features over 140 pictures, most of which have never been published before. The book concludes by looking at the ambitious plans for new high-speed networks, connecting both countries, and most of their neighbors by the late 2030s."--Nakladatelská anotace